A possibilidade da realização do negócio jurídico processual na recuperação judicial - Paiva, Vanessa Cristina André de (2020)
We will analyze the compatibility of the application of the procedural legal agreement, provided in articles 190 and 191 of the Civil Procedure Code, in the procedure of judicial reorganization of companies, regulated by Law nº. 11.101 / 05. The scientific work will be based on the analysis of the procedural legal agreement, its historical context and evolution, requirements, ways of accomplishment, hypotheses of invalidation, as well as we will analyze the procedure of the judicial reorganization of companies disciplined by Law 11.101 / 05 the requirements for its grant, purpose, applicable legal principles and, finally, we will analyze, from a scientific point of view, the possibility of applying the procedural legal agreement in the judicial recovery procedure, addressing recent decisions on the subject.